Application of the dynamical damper in a piecewise linear system - Zaksienė, Genovaitė (Lietuvos matematikos rinkinys, 2002)
The linear dynamical damper of nonlinear system functions better than in linear system. It can compensate excitation in the wild diapason of frequency.